The sculpture of F.E. McWilliam - Ferran, Denise; Holman, Valerie (Farhham, Surrey Burlington, Vermont Lund Humphries Much Hadham, Hertfordshire In association with the Henry Moore Foundation, 2012)
A highly respected sculptor, F.E. McWilliam (1909-1992) was described by Bryan Robertson in 1992 as 'one of the truest artists to work in England this century'. Yet despite achieving great acclaim in his lifetime, McWilliam's contribution to modern art has been unduly neglected in recent years.
Keywords: McWilliam, F. E. -- 1909-1992 -- Criticism and interpretation; Sculpture -- Great Britain -- 20th century